Deception in Amber Heard and Johnny Depp’s Trials (Journal of the College of Education for Women, 2023)
Deception is defined as a linguistic and non-linguistic behavior that is used in interaction in order to make the addressees believe what is believed to be false or lack evidence. McCornack (1992) classifies deception into four manipulative strategies (i.e., fabrication, distortion, equivocation and concealment), other scholars argue that deception encompasses the strategies of “fabrication (outright lying), equivocation (being vague and ambiguous), or concealment (with holding relevant information) Thus, the present study investigates the deception strategies and motives that are used by Johnny Depp and Amber Heard during their defamation trials. Qualitative and quantitative methods are employed when analyzing the data in question. The first method is achieved via using Buller & Burgoon’s (2004) strategies of deception and Ekman’s (1995) motives of deception, while the second method is achieved via counting frequencies and percentages. It is found that the strategies of fabrication and equivocation are frequently used by Johnny Depp, while the strategies of fabrication and concealment are frequently used by Amber Heard. It is concluded that deception can be achieved via using the strategy of fabrication in order to avoid embarrassment, get rid of an awkward situation and get the admiration of others.